Taḥlīl Ma‘nā al-Ughniyah “Kalām ‘Aynayh” ‘alā Asās Naẓariyyat Firdīnān dī Sūsīr fī ‘Ilm al-Dalālah: An Analysis of the Meaning of the Song “Kalam Eineh” Based on Ferdinand de Saussure’s Theory in Semantics - Firda Aulia Denisa; Wahdah Wulidatus S.N; Muzamil R Pawi (Critical Review of English-Arabic World Journal, 2026)
Songs, as an artistic form that expresses emotions and experiences, often reflect culture and profound meanings through their lyrics. This study analyzes the lyrics of the song “Kalam Eineh” by Sherine Abdel Wahab using Ferdinand de Saussure’s semiotic theory, which focuses on denotative and connotative meanings. This research aims to reveal how the song lyrics represent the meaning of love, both literally and implicitly, as well as how social and cultural contexts influence their interpretation. The research method used is a descriptive qualitative approach, with data collection techniques in the form of document analysis and in-depth observation of the song lyrics. The findings show that the lyrics portray love as sacrifice, sincerity, and deep openness, strengthened by cultural symbols and personal emotions. This analysis confirms that the meaning of song lyrics is not limited to verbal communication, but also serves as a reflection of universal values and experiences.